2022
DOI: 10.3390/foods11131929
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characterization of Different Parts of Broiler and Ligor Hybrid Chickens

Abstract: The quality characterization of different parts of male and female Ligor hybrid chickens was investigated and compared with those of commercial broiler. Genotypes, muscle types, and sex had effects on the composition, physicochemical, and textural properties of chicken samples. Ligor hybrid chicken contained higher percentages of protein, moisture, ash, and collagen content but lower fat content than those of commercial broiler (p < 0.05), except in the case of breast, where no significant difference in moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…As observed in the results, the content of crude protein was higher in the pectoral than thigh muscle ( p < 0.05). This was compatible with previous research [ 26 , 27 ]. It indicates that the protein nutritional value of the pectoral muscle is higher than that of the thigh muscle.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As observed in the results, the content of crude protein was higher in the pectoral than thigh muscle ( p < 0.05). This was compatible with previous research [ 26 , 27 ]. It indicates that the protein nutritional value of the pectoral muscle is higher than that of the thigh muscle.…”
Section: Discussionsupporting
confidence: 94%
“…We found that the thigh muscle had a higher moisture and CF than those of the pectoral muscle in all age groups, and this result was more pronounced in the case of female chickens. These results were also observed in Panpipat’s study, while there was no difference between the genders in their study [ 26 ]. Thus, the thigh muscle may have a better texture than the pectoralis of Guangyuan grey chicken.…”
Section: Discussionsupporting
confidence: 75%
“…Within the gross nutrient cluster, protein presented the highest discriminant potential. Indigenous chickens have been reported to usually present progressively higher protein levels as they age [ 177 ]. In this way, the high variability in the slaughter age variable also caused the protein content to vary across the genotypes that were sampled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the high variability in the slaughter age variable also caused the protein content to vary across the genotypes that were sampled in this study. Nevertheless, the conditioning effects of other factors such as genotype and sex on protein content cannot be discarded, as suggested by the literature [ 177 , 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ITL muscle in hens has lower collagen content than Silky and White Leghorn cockerels. In broiler chickens, collagen content in the thigh muscle is higher in males than in females, but not in the breast muscle at 14 weeks of age[ 10 ]. Considering such differences, it may be useful to examine the difference in gene expression levels of collagen and related stimulating factors to clarify them, but few studies to date have done so.…”
Section: Introductionmentioning
confidence: 99%